Implementasi Strategi CRM dan Penggunaan Digital Marketing pada UMKM di Credit Union Madani Kotabumi Tangerang - Cynthia; Anisya, Cindy; Widya, Devania; Silaswara, Diana; Lenggo Ginny, Puti; Susanti, Metta; Winata, Suryadi; Limajatini (LP3kM Universitas Buddhi Dharma, 2022)
This student creativity development activity was carried out based on the collaboration between the Faculty of Business, Buddhi Dharma University and KSP Madani which was held at KSP Madani Credit Union Kotabumi, Tangerang City. Banten Province. The training participants are UMKM members of cooperatives, and the activities are carried out within a period of three months, with training activities planned in the form of focus group discussions, material presentations and interactive question-and-answer between the giver of materials and training and mentoring participants. The material provided was in accordance with the needs requested by KSP Madani at the beginning of the meeting, namely knowledge and implementation of Customer Relationship Management (CRM) for UMKM actors under the guidance of KSP Credit Union Madani. Participants from the training are members of the Madani cooperative, which are UMKM business actors in the Culinary and Services sector The output plan of this student creativity development activity is in the form of improving the performance of cooperative management.